2021
DOI: 10.1080/13501763.2021.1912149
|View full text |Cite
|
Sign up to set email alerts
|

Honesty pledges for the behaviorally-based regulation of dishonesty

Abstract: A common dilemma in regulation is determining how much trust authorities can place in people's self-reports, especially in regulatory contexts where the incentive to cheat is very high.In such contexts, regulators, who are typically risk averse, do not readily confer trust, resulting worldwide in excessive requirements when applying for permits, licenses, and the like. Studies in behavioral ethics have suggested that asking people to ex-ante pledge to behave ethically can reduce their level of dishonesty and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 63 publications
1
15
1
Order By: Relevance
“…Peer and Feldman (2021) also found that pledges are significantly effective across individual differences.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Peer and Feldman (2021) also found that pledges are significantly effective across individual differences.…”
mentioning
confidence: 86%
“…Beck (2021) finds that subjects who take decisions fast tend to tell the truth more under oath. Peer and Feldman (2021) show that honesty pledges reduce dishonesty significantly and when it is combined with fines, it is more effective. One neutral result is that oaths do not reduce dishonesty on a group level (Krüger and Van Geen, 2016).…”
Section: Framework Related Literature and Hypothesesmentioning
confidence: 97%
“…For example, Bonfim and Silva (2019) found that informing groups that their reported die rolls might be subject to an audit, which would reduce their earnings to zero if caught cheating, reduced dishonesty from 27% to 9%. Similarly, Peer and Feldman (2021) studied the effect of fines and honesty oaths on dishonest behavior. They found that both fines and committing to an honesty oath increased honesty.…”
Section: Punishmentmentioning
confidence: 99%
“…We assign these future managers to always be in the role of the Sender, and we 1 While the control over the environment offered by a laboratory experiment is better suited to testbed the effect of the oath on future managers, it raises the obvious concern of whether these results would extend to a non-laboratory setting. On this issue, we refer the reader to the literature that correlates lying in lab experiments to unethical behavior in the field (e.g., Potters and Stoop, 2016;Dai et al, 2017;Hanna and Wang, 2017;Cingl and Korbel, 2020) and the ones that investigate both truth-telling behavior under oath in the context of field experiments (Carlsson et al, 2013;Koessler et al, 2019;Jacquemet et al, 2021) ot the long-lasting effects of promises (Peer and Feldman, 2021). 2 An alternative interpretation of the effect of the oath is the idea that it simply primes subjects to truth-telling.…”
Section: Introductionmentioning
confidence: 99%